Lanceola felina Bovallius 1885 - Zeidler, Wolfgang (Zenodo, 2019)
Lanceola felina Bovallius, 1885 Southeast Pacific: 1090294 , 5/310, [58°51’S 70°28’W], 1419 m. Remarks : This species mainly inhabits circum-tropical waters but in the Atlantic it has been recorded as far south as Tristan de Cuhna (about 37°S). It also mainly prefers surface waters. This is the first record from the Southern Ocean, from great depth. Its occurrence there may be because of the incursion of warm water as it is at the extreme southern range of the sub-Antarctic Zone. Published as part of Zeidler, Wolfgang, 2019, New and additional records of hyperiidean amphipods of the infraorder Physosomata (Crustacea: Amphipoda: Hyperiidea) from the Antarctic Zone of the Southern Ocean, pp. 510-520 in Zootaxa 4576 (3) on page 512, DOI:10.11646/zootaxa.4576.3.5, http://zenodo.org/record/3715770